2007
DOI: 10.1038/sj.ejhg.5201799
|View full text |Cite
|
Sign up to set email alerts
|

Heritable skewed X-chromosome inactivation leads to haemophilia A expression in heterozygous females

Abstract: Factor VIII gene, F8, mutations cause haemophilia A (HA), an X-linked recessive disorder. Expression in heterozygous females has been ascribed to skewed X-chromosome inactivation (XCI). To investigate the cause of HA in three heterozygous females within an Atlantic Canadian kindred, the proband (severely affected girl, FVIII activity: 2%) and 17 relatives across three generations were studied. F8 genotype, FVIII activity, XCI ratio (XCIR) (paternal active X: maternal active X), karyotype, submegabase resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 28 publications
2
66
0
1
Order By: Relevance
“…7,8 Naumova et al 9 used an approach of classic linkage analysis, to show that markers DXS425 (Xq25) and DXS294 (Xq26) are likely linked to the human XCE. Cau et al used a similar approach to identify a candidate region of 4.2Mb cM ranging from DXS8067 (Xq24) to DXS8057 (Xq25), which partially overlaps the region identified by Naumova et al 7 In a previous report, 10 we described a family with three males and three females with clinical symptoms of haemophilia A, a bleeding disorder caused by low factor VIII activity. We showed that the three affected females had XCI ratios skewed toward activation of the mutated X-chromosome and that the degree of skewing correlated with FVIII activity and the severity of disease in all carriers in the family.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…7,8 Naumova et al 9 used an approach of classic linkage analysis, to show that markers DXS425 (Xq25) and DXS294 (Xq26) are likely linked to the human XCE. Cau et al used a similar approach to identify a candidate region of 4.2Mb cM ranging from DXS8067 (Xq24) to DXS8057 (Xq25), which partially overlaps the region identified by Naumova et al 7 In a previous report, 10 we described a family with three males and three females with clinical symptoms of haemophilia A, a bleeding disorder caused by low factor VIII activity. We showed that the three affected females had XCI ratios skewed toward activation of the mutated X-chromosome and that the degree of skewing correlated with FVIII activity and the severity of disease in all carriers in the family.…”
Section: Introductionmentioning
confidence: 91%
“…The family studied here (Figure 1) is as we have previously described, 10 with the addition of seven new family members, II.4, II.10, III.4, III.6, III.7, IV.I and IV.2.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations